A luminescent Pt2Fe spin crossover complex. Issue 7 (30th January 2017) - Schäfer, Bernhard; Bauer, Thomas; Faus, Isabelle; Wolny, Juliusz A.; Dahms, Fabian; Fuhr, Olaf; Lebedkin, Sergei; Wille, Hans-Christian; Schlage, Kai; Chevalier, Katharina; Rupp, Fabian; Diller, Rolf; et al.
Abstract : A heterotrinuclear luminescent [Pt2 Fe] spin crossover (SCO) complex was developed, synthesized, and investigated. Abstract : A heterotrinuclear [Pt2 Fe] spin crossover (SCO) complex was developed and synthesized employing a ditopic bridging bpp-alkynyl ligandL and alkynyl coordinated Pt II terpy units: [Fe II (L-Pt II )2 ]2 (BF4 )2 (1 ). We identified two different types of crystals of1 which differ in their molecular packing and the number of co-crystallized solvent molecules:1 H (1 ·3.5CH2 Cl2 in P 1̄) and1 L (1 ·10CH2 Cl2 in C 2/ c ); while1 L shows a reversible SCO with a transition temperature of 268 K, the analogous compound1 H does not show any SCO and remains blocked in the HS state. The temperature-dependent magnetic properties of1 H and1 L were complementarily studied by Mössbauer spectroscopy. It has been shown that1 L performs thermal spin crossover and that1 L can be excited to a LIESST state. The vibrational properties of1 were investigated by experimental nuclear resonance vibrational spectroscopy. The experimentally determined partial density of vibrational states (pDOS) was compared to a DFT-based simulation of the pDOS. The vibrational modes of the different components were assigned and visualized. In addition, the photophysical properties of1 andL-Pt were investigated in the solid state and in solution. The ultrafast transient absorption spectroscopy of1 in solution was carried out to study the PL quenching channel via energy transfer from photoexcited Pt II terpy units to the Fe II -moiety.